ECMO treatment on patients with respiratory failure because of COVID-19 and improvement of the clinical condition (Research, Society and Development, 2021)
Extracorporeal membrane oxygenation (ECMO) has been widely used in patients with severe respiratory failure caused by the new coronavirus (COVID-19). In those people, the pulmonary interstice is occupied by cells and inflammatory substances, which impairs gas exchange and causes hypoxemia. The ECMO treatment consists of boosting the blood of the person through a cannula to an artificial membrane capable of oxygenating it, which is then able to return to the body. The present study aimed to identify, on patients with respiratory failure due to COVID-19, whether the ECMO treatment compared to standard therapy provides improvements in the clinical condition. A systematic review of the literature was conducted in May 2021. The research was done in two databases: PubMed and BVS. From the resulting articles, 7 were selected because they fit the research criteria. From the analysis of the results, it was found that ECMO treatment is able to reduce the mortality of patients with severe respiratory failure when compared to other treatments. When used, this resource proved to be able to reduce the amount of inflammatory substances and the storm of cytokines, thus enabling improvement in the oxygen supply to vital organs and avoiding lung injuries resulting from mechanical damage. In addition, when used in conjunction with medications, it showed a reduction in inflammation. Therefore, it was perceived that ECMO is a good alternative to patients, but not when used alone. It is necessary to supplement treatment with medications that relieves the symptoms.